Proton-induced DNA damage promotes integration of foreign plasmid DNA into human genome - Katerji, Meghri; Bertucci, Antonella; Filippov, Valery; Vazquez, Marcelo; Chen, Xin; Duerksen-Hughes, Penelope J. (Frontiers in Oncology, 2022)
High-risk human papillomaviruses (HPVs) cause virtually all cervical cancer cases and are also associated with other types of anogenital and oropharyngeal cancers. Normally, HPV exists as a circular episomal DNA in the infected cell. However, in some instances, it integrates into the human genome in such a way as to enable increased expression of viral oncogenes, thereby leading to carcinogenesis. Since viral integration requires breaks in both viral and human genomes, DNA damage likely plays a key role in this critical process. One potentially significant source of DNA damage is exposure to elevated doses of ionizing radiation. Natural background radiation is ubiquitous; however, some populations, including radiological workers, radiotherapy patients, and astronauts, are exposed to significantly higher radiation doses, as well as to different types of radiation such as particle radiation. We hypothesize that ionizing radiation-induced DNA damage facilitates the integration of HPV into the human genome, increasing the risk of developing HPV-related cancers in the exposed population. To test this, we first determined the kinetics of DNA damage in keratinocytes exposed to ionizing radiation (protons) by assessing γ-H2AX foci formation using immunofluorescence (direct damage), and also measured ROS and 8-oxoG levels via DCFDA and Avidin-FITC (indirect damage).As anticipated, direct DNA damage was observed promptly, within 30 min, whereas indirect DNA damage was delayed due to the time required for ROS to accumulate and cause oxidative damage. Although radiation was lethal at high doses, we were able to establish an experimental system where radiation exposure (protons and X-rays) induced DNA damage dose-dependently without causing major cytotoxic effects as assessed by several cytotoxicity assays. Most importantly, we explored the impact of radiation exposure on integration frequency using a clonogenic assay and demonstrated that as predicted, proton-induced DNA damage promotes the integration of HPV-like foreign DNA in cervical keratinocytes. Overall, the insights gained from this work enable us to better understand the contribution of radiation exposure and DNA damage to HPV-mediated carcinogenesis and direct us toward strategies aimed at preventing malignancies in HPV-infected individuals.